PRO DAN KONTRA PENERAPAN ASEAN OPEN SKY BAGI NEGARA ANGGOTA ASEAN - Prasetyo, Dedi (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2020)
Flight liberalization in South East Asia Region has long been initated and implemented since 2015 under the name of ASEAN Open Sky Policy. The implementation of this policy which is aimed to give a full access to the flight companies in ASEAN countries triggers a debate. There are pros and cons about it. Through this research, the writer intends to analyse cost and benefit of the implementation of that policy to the ASEAN countries. The focus of the analysis is on the impact of ASEAN Open Sky Policy to the countries in the region where the policy contributes to the ASEAN Economic Community. This research uses liberal institutional approach. The method is literature studi. Data processing technique uses single SWOT analytic concept. The result shows that the effect of ASEAN Open Sky is more beneficial to Singapore and Malaysia rather than to Indonesia and the Philippines.